A kid is a kid is a kid - O'Leary, Sara (Groundwood Books/House of Anansi Press, 2021)
"In this companion to the enormously popular A Family Is a Family Is a Family, a group of kids share the silly questions they always hear, as well as the questions they would rather be asked about themselves. Being the new kid is hard, a child in the school playground tells us. I can think of better things to ask than if I'm a boy or a girl. Another child comes along and says she gets asked why she always has her nose in a book. Someone else gets asked where they come from. One after another, children share the questions they're tired of being asked again and again -- as opposed to what they believe are the most important or interesting things about themselves. As they move around the playground, picking up new friends along the way, there is a feeling of understanding and acceptance among them. And in the end, the new kid comes up with the question they would definitely all like to hear: "Hey kid, want to play?" Sara O'Leary's thoughtful text and Qin Leng's expressive illustrations tell a story about children who are all different, all themselves, all just kids."--